Sound waves in fluidized bed using CFD–DEM simulations - Khawaja, Hassan (UiT The Arctic University of Norway, 2018)
The seminar is about modelling sound waves in a fluidized bed using CFD–DEM numerical simulations. The presented case includes the application of appropriate initial and boundary conditions to reproduce bed phenomena and the effect of varying the bed height. The results of the simulations matched those from the literature. The pressure and particle velocity profiles obtained feature oscillatory behaviour to which functions (based on a damped standing wave) were fitted, enabling an explicit dependence on time and space variables to be established. These fitted functions were substituted into the linearised governing equations for the two-phase flow. These solutions enabled a new relationship to be derived for the speed of sound and damping in the system. The conclusion drawn is that the damping in the system is governed by the effective bulk viscosity of the solid phase, which arises from the particle viscosity.